Ticagrelor for the treatment of atherosclerotic disease: insights from the PARTHENON clinical development program. (July 2016) - Held, Peter; Himmelmann, Anders; Ditmarsch, Marc
Ticagrelor (P2Y12 receptor antagonist) is presently indicated for preventing atherothrombotic events in patients with acute coronary syndrome and patients with a history of myocardial infarction. The PARTHENON clinical development program comprises five randomized, controlled, cardiovascular, indication-seeking outcome studies, aiming to evaluate ticagrelor across the spectrum of patients with atherothrombotic disease. Results of two large-scale trials support a benefit for ticagrelor in patients with acute coronary syndrome (PLATO; ClinicalTrials.gov: NCT00391872) and in patients with a history of myocardial infarction (PEGASUS-TIMI 54; ClinicalTrials.gov: NCT01225562). Ongoing trials will provide information on the efficacy and safety of ticagrelor in patients with acute ischemic stroke or transient ischemic attack (SOCRATES; ClinicalTrials.gov: NCT01994720), peripheral artery disease (EUCLID; ClinicalTrials.gov: NCT01732822) and coronary artery disease in patients with Type 2 diabetes mellitus (THEMIS: ClinicalTrials.gov: NCT01991795).